Elementary School Teachers’ Acceptance of Website-Based Multimodal Media: A SUS Analysis - Adestipa; Abidin, Yunus; Kurniawan, Dede Trie (International Conference on Elementary Education, 2025)
The rapid advancement of educational technology has introduced various innovations, yet the acceptance and readiness of elementary school teachers to adopt AI-based learning media remain inconsistent. Limited pedagogical understanding and diverse levels of technological literacy continue to hinder effective integration. This study examines teachers’ acceptance of a website-based multimodal learning medium developed through a deep learning approach. The medium integrates text, images, audio, and video within an adaptive web-based system designed to enhance students’ learning experiences. A quantitative survey method was employed, utilizing the System Usability Scale (SUS) questionnaire administered to 80 elementary school teachers in Bandung Regency, Indonesia. The findings revealed an average SUS score of 78, classified as “good” and approaching the “widely accepted” level. Respondents perceived the medium as effective, engaging, and aligned with twenty- first-century learning competencies. Overall, the results demonstrate that the application of deep learning in designing adaptive multimodal learning environments holds significant promise for broader adoption in elementary education contexts.